Carnal legalities: affective lives within zones of counter-terrorism operation. Issue 4 (December 2018) - Kvedaravicius, Mantas
Abstract This article emerges from the anthropological fieldwork carried out in the eastern Ukraine from 2014 to 2015 and in the Chechen Republic of the Russian Federation between 2006 and 2009. Both locales, at a time of the research, were marked by proximity of the ongoing armed conflicts, and were legally defined as the "Zones of Counter-Terrorism Operation". The legal status of the Zones not only suspended a number of laws and created new forms of violence, but also coexisted with the sense of everyday life being "normal" in spite of immanent albeit usually covert violence of ongoing disappearances and torture. Moreover, sustaining the status of the zones necessitated the systematic production of terrorists that depended on the massive fabrications of legal cases that in their own right relied on confessions and signatures acquired under torture or, quite often, on the killing and kidnapping of young men to present them as exterminated terrorists. This article does not present a comparative study between Chechen and eastern Ukrainian armed conflicts. Instead, it engages ethnographically with the notion ofbespredel, literally limitlessness, which in these post-soviet spaces define affective conditions of life and is evoked to designate the unjust or violent actions of state agents. The article insists that the modalities of legal operations cannot be adequately understood through the analytical concepts of the "state of exception" and "thanatopolitics"; such do not pay sufficient attention to the short circuits and affectivity of the power effects. Rather, the article asks what kind of corporealities and sensibilities are presupposed, effected or failed to be so under such circumstances.